Inibidores do SGLT-2 - Silva-Cardoso, José (2021)
Funding Information: José Silva-Cardoso has received speaker and consultant fees, advisory board participation fees, or investigational grants from Abbott, AstraZeneca Pharmaceuticals, Bial, Boehringer Ingelheim, Menarini, Merck Serono, Merck Sharp & Dohme, Novartis, Orion, Pfizer, Sanofi, Servier, and Vifor Pharma. Aurora Andrade has received speaker or advisory boards fees from Novartis, AstraZeneca, Servier, Orion and Bial. Dulce Brito has received speaker and consultant fees or investigational grants from AstraZeneca Pharmaceuticals, Boehringer Ingelheim, Novartis, Orion, Pfizer, Roche Diagnostics, Sanofi, Servier, and Vifor Pharma. Jorge Ferreira has received speaker and consultant fees from Amgen, AstraZeneca, Boehringer-Ingelheim, Novartis. Cândida Fonseca has received speaker and consultant fees, or investigational grants, from AstraZeneca Pharmaceuticals, Bayer, Boehringer Ingelheim, Merck Serono, Novartis, Orion, Pfizer, Sanofi, Servier, and Vifor Pharma. Marisa Peres has received speaker or advisory board fees from AstraZeneca, Servier, and Novartis. Fátima Franco has received speaker or advisory board fees from Boehringer, AstraZeneca, Novartis and Servier. Brenda Moura has received speaker or advisory board fees from AstraZeneca, Boehringer Ingelheim, Eli Lilly, Servier, Novartis, Vifor Pharma. Publisher Copyright: © 2021 Sociedade Portuguesa de Cardiologia Copyright: Copyright 2021 Elsevier B.V., All rights reserved.